The use of real-world data in cancer drug development. (September 2018) - Skovlund, E.; Leufkens, H.G.M.; Smyth, J.F.
Abstract: Excitement about the dramatic increase in potential successful anticancer medicines in recent years is hampered by the high costs involved as well as the length of time traditional pathways take for regulatory approval. The translation of experimental clinical data into real-world evidence is also problematic. While the randomised controlled trial remains the gold standard for assessing efficacy and safety, there is increasing interest in the use of observational data to enable more rapid, informed and widespread availability and access to important anticancer medicines. Taking real-world evidence into account in regulatory and health technology assessment in a thoughtful and balanced fashion will enrich and justify sound decision-making. Highlights: Adding real-world data to randomised controlled trials of anticancer drugs can increase external validity. Many challenges remain before real-world evidence may become an integrated part of decision-making in drug development. Even the use of advanced strategies to adjust for confounding factors may lead to biased efficacy estimates. Use of RWD could reduce costs, minimise patient numbers in randomised trials and supplement or confirm results from RCTs.